2020
DOI: 10.1371/journal.pone.0243068
|View full text |Cite
|
Sign up to set email alerts
|

The association between triglycerides and ectopic fat obesity: An inverted U-shaped curve

Abstract: Background Ectopic fat obesity and triglycerides are risk factors for diabetes and multiple cardiovascular diseases. However, there have been limited studies on the association between triglycerides and ectopic fat obesity. The purpose of this study was to explore the association between triglycerides and ectopic fat obesity. Methods and results In this cross-sectional study, we retrospectively analyzed 15464 adult participants recruited by Murakami Memorial Hospital (8430 men and 7034 women, average age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 33 publications
3
26
0
1
Order By: Relevance
“…The formulas for calculating obesity and lipid-related indices are shown in Fig. 1 [13][14][15][16][17][18][19][20][21].…”
Section: Data Collection and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The formulas for calculating obesity and lipid-related indices are shown in Fig. 1 [13][14][15][16][17][18][19][20][21].…”
Section: Data Collection and Measurementmentioning
confidence: 99%
“…In this context, a number of simple anthropometric indicators, biochemical indicators, and some combination of indicators, and even complex digital models have been developed to assess NAFLD risk. Among them, obesity and lipid-related indices are the most effective markers for predicting NAFLD and are widely used in epidemiological studies, including triglyceride (TG), conicity index (COI), visceral adiposity index (VAI), triglyceride-glucose (TyG) index, body roundness index (BRI), body mass index (BMI), hepatic steatosis index (HSI), waist circumference (WC), body-shape index (ABSI), waist-toheight ratio (WHtR), lipid accumulation product (LAP), triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio, and TyG index-related parameters (TyG-WHtR, TyG-BMI, TyG-WC) [12][13][14][15][16][17][18][19][20][21]. At present, there are very few comparative studies on the prediction of NAFLD by obesity and lipid-related indices.…”
Section: Introductionmentioning
confidence: 99%
“…With changes in social structure, lifestyle and diet, some subtle changes have taken place in the human body structure, especially fat storage, which has increased significantly [ 37 , 38 ]. Relying solely on BMI to distinguish obesity cannot reflect this information [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of the lipid depot from multilocular to unilocular has been reported in brown adipocytes in obesity; the change from BAT to WAT is known as whitening [7,8]. Excess and ectopic fat accumulation, including BAT whitening, are major risk factors for the development of hyperlipidemia, type 2 diabetes, and cardiovascular disease [9]. Previous studies have reported that BAT whitening is associated with downregulation of mitochondrial proteins [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…BAT whitening attenuates energy consumption and accelerates the progression of obesity [9,28,29]. Therefore, inhibition of BAT whitening in childhood is important to decrease the incidence of obesity in adulthood.…”
Section: Introductionmentioning
confidence: 99%